Effects of Descurainia sophia on Oxidative Stress Markers and Thirst Alleviation in Hemodialysis Patients: A Randomized Double-Blinded Placebo-Controlled Cross-Over Clinical Trial. (4th November 2022) - Asgharpour, Masoumeh; Enayati, Noora; Rezaei Sadrabadi, Mohammad; Mohamadi Afrakati, Mana; Khavandegar, Armin; Mardi, Parham; Alirezaei, Amirhesam; Taherinia, Ali; Bakhtiyari, Mahmood
Abstract : Background . Patients undergoing hemodialysis (HD) are regularly exposed to oxidative stress and inflammation and may suffer from thirst distress with no definitive treatment to address these complications. Descurainia sophia (DS) has been used to alleviate thirst in traditional Persian medicine. This study aimed to assess the effectiveness of DS on oxidation factors and thirst score in HD patients. Methods . This study was conducted on fifty-three HD patients referred to Tehran Shahid Modarres hospital. The patients were randomly divided into two groups: Group 1 received DS for six weeks, then underwent four weeks of washout period followed by six weeks of placebo treatment, while group 2 received placebo initially followed by treatment with DS. Biochemistry, malondialdehyde (MDA), and total antioxidant capacity (TAC) were measured in four phases: at the beginning, before washout, after washout, and at the end of the study. The patient's body weight was recorded at the start of each session to assess interdialytic weight gain. Thirst scores also were measured using a visual analog scale. Results . A total of 53 patients, including 23 (43.4%) male and 30 (56.6%) female subjects, were included in the study. The results showed a reduction in thirst score (p = 0.001 ), cholesterol levels (p = 0.046 ), triglycerides (0.003), and MDA (p < 0.001 ) following the four-week administration of DS treatment in HD patients. The mean levels of TAC were increased (p < 0.001 ), and calcium, as well as Na+, remained unchanged (p > 0.05 ). Also, a significant decrease in the patient's weight was observed (p value <0.001). This effect persisted after shifting to a placebo. However, the two groups had no significant difference (p value = 0.539). Conclusion . DS powder-mixed syrup may benefit HD patients by facilitating free radical scavenging and alleviating thirst distress with minimal adverse effects. The seeds could therefore be utilized as a complementary therapy for hemodialysis patients.